Implementation of Pluralism Values in Indonesia and Its Relevance to The Medina Charter - Ghozali, Abdul Malik; Zaeny, Ahmad (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2019)
Violence due to religious conflict is still becoming one of the problems faced by almost all countries, including Indonesia. Religious doctrine is often understood so narrowly that it imprisons its adherents in religious exclusivism and triggers conflict. In the context of a pluralistic Indonesian society, anticipatory efforts need to be made so that violence in the name of religion can be avoided. One of the efforts is by strengthening the values of pluralism. This article examines the implementation of the values of pluralism among the people of the village of Hanura Pesawaran Lampung while looking for its relevance to the values of pluralism that exist in the Medina Charter. This study is a field research using a qualitative approach. This study is field research using a qualitative approach. Data were obtained by observing, documenting, and interviewing community leaders in the village of Hanura. The results showed that the people of Hanura village had implemented pluralism values well. This can be seen from three indicators, namely: recognition of equal rights and obligations, the existence of social coherence, and community tolerance. These three things are following the values of pluralism in the Medina Charter. In conclusion, the life of Hanura villagers can be used as a model of the implementation of the values of pluralism in society.